Viscoelastic properties of the human tear film. (June 2022) - Recchioni, Alberto; Mocciardini, Emanuele; Ponzini, Erika; Tavazzi, Silvia
Abstract: When considering eye blinking from a tribological perspective, tear viscosity is expected to play a fundamental role. The application of rheological techniques to describe the tear film dates back to the late 1980s, but there has been a continuous need of reappraisal due to new findings in tear film biochemistry and to the development of new methods of physico-chemical characterization. This review provides an overview on tear rheological behavior by analyzing the peer-reviewed literature on this topic. Specifically, examples of in-vitro and in-vivo viscosity measurements are detailed, highlighting experimental criticalities and the need of a standard convention for rheological techniques to compare data across different studies, of analyses on tears of single individuals even within the limits of the low volume available, and of a further development of in-vivo techniques. Then, the controversial role of specific tear components on viscosity is discussed, together with the alterations associated to dry eye disease and contact lens wear. Finally, an updated focus is reported on the viscosity of artificial tears formulations. Highlights: Tear viscosity is governed by complex interactions between different constituents. In-vitro viscosity analysis methods on microliters of tears were recently proposed. Further developments of in-vivo viscosity analysis methods are desirable. Dry eye disease and contact lens wear typically cause tear viscosity alterations. The constituent molecular weight distribution influences eyedrop viscosities.